Dynamic Resource Allocation Algorithm for UAV Emergency Communication Network Based on Energy Balance - Wang, Jinyu (2023 IEEE 3rd International Conference on Electronic Technology, Communication and Information (ICETCI), 2023)
With the development of network communication, wireless networks are increasingly demanding architectures that support high throughput, super reliability, low energy consumption, and diverse applications. Due to the progress of UAV technology and the reduction of cost, the global market of UAV has developed rapidly in the past decade, and its market space and application potential are huge. Unmanned aerial vehicle (UAV) has high flexibility and rapid deployment ability, and can provide flexible and efficient services for emergency communication and post-disaster rescue. Unmanned aerial vehicle (UAV)-assisted wireless network can greatly improve the system performance by dynamically adjusting its position, thus overcoming the related defects caused by the fixed traditional wireless communication architecture. Unmanned aerial vehicle (UAV) has unique flexibility, maneuverability and can work normally in complex environmental conditions, etc. At present, many human applications that cannot be directly realized in dangerous areas rely on UAV, which has attracted more and more attention. UAV has developed many applications in fields such as aerial surveillance, aerial photography, precision agriculture, traffic control, search and rescue, parcel delivery, telecommunications and so on. Network management is to cope with the increasing complexity of the network, liberate manpower from tedious machine management, and save manpower cost. At present, the information about network management in emergency communication system is limited. As an important part of the emergency communication system, the network management system has great practical significance for improving the information level, reducing the losses in the affected areas and saving the lives of the affected people.